Communicating The Smart City Concept to The SME Community - Pupung Arifin; Jessica Amanda Putri (School of Communication Science and Media Business, 2024)
The smart city concept has been used by many cities in Indonesia as means to ease people lives. Yogyakarta, as the province with the highest ratio of area and number of tourism visits in Indonesia, is a province that has been quite hit by the COVID-19 pandemic. One of the affected parties are Small and Medium Enterprises (SMEs). To anticipate this, the Yogyakarta City Government launched the Jogja Smart Service (JSS) application. JSS was launched with the aim of facilitating public services, and one of its features namely Gandeng Gendong to bring together the SMEs community with potential buyers. This paper will describe the communication process of JSS application by Yogyakarta City Government and SMEs actors. This research departs from the impact of the Covid-19 pandemic felt by the SMEs of Yogyakarta City on the economy in their lives. After the pandemic, the Yogyakarta City Government tried to foster smart economy as one of the smart city branch concepts. Nonetheless, there are still many challenges. In anticipation of a repeat of the economic impact of the COVID-19 pandemic, the SMEs actors must be able to quickly adopt the Jogja Smart Service application. The results of the research obtained are the process of communication by Yogyakarta City Government and SMEs actors in the early majority stage. The SMEs actors are at the confirmation stage. The confirmation determines that SMEs actors continue to use the Jogja Smart Service application but need more socialization and training.